2021
DOI: 10.21608/ejchem.2021.85969.4163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of Low Calories Ice Cream Properties Prepared By Using Fat Replacer And Sweetener

Abstract: Producing ice cream suitable for individual people is a recent demand. Low calories or reduced fat-ice-cream has great request for avoiding obesity and heart diseases. In the present research; Etenia 457 was used as fat replacer while Sativosidewas used as sweetener at different levels (0, 25, 50, 75 and 100%) to achieve five treatments, namely C, T1, T2, T3 and T4 respectively. Maltodextrin and Sorbitol (1:2 W/V) as bulking agent were also added. The obtained results showed no clear variations in the total so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…It was noted from the results of the presence of a clear effect of the WPC addition in improving viscosity characteristics and directly proportional to the increase in the percentage added, and this is consistent with Gokhale et al (2018), who indicated that adding WPC to low-fat food products significantly improves their body and texture, and this improves viscosity. Also, Abbas et al (2022) stated that using WPC in the production of fat-free dairy sweeteners has increased the product's viscosity and significantly improved its sensory properties due to WPC's ability to bind water. The viscosity of the C+ treatment was higher compared to other treatments, and this was consistent with Garcia et al (2023), who reported that the high viscosity of the cream control treatment compared to the cream treatments supported either skim milk or low melting butterfat.…”
Section: Viscositymentioning
confidence: 99%
“…It was noted from the results of the presence of a clear effect of the WPC addition in improving viscosity characteristics and directly proportional to the increase in the percentage added, and this is consistent with Gokhale et al (2018), who indicated that adding WPC to low-fat food products significantly improves their body and texture, and this improves viscosity. Also, Abbas et al (2022) stated that using WPC in the production of fat-free dairy sweeteners has increased the product's viscosity and significantly improved its sensory properties due to WPC's ability to bind water. The viscosity of the C+ treatment was higher compared to other treatments, and this was consistent with Garcia et al (2023), who reported that the high viscosity of the cream control treatment compared to the cream treatments supported either skim milk or low melting butterfat.…”
Section: Viscositymentioning
confidence: 99%